Visual Prostate Symptom Score: Questioning Its Feasibility in The Scenario of a Tertiary Health Care Center of Central Nepal - Timilsina, Bhusan Raj; kafle, Aayush; Giri, Saroj; Mahaseth, Naveen; Sah, Nirmal prasad; Pradhan, Sulav; KC, Sudeep Raj; Ghimire, Rupak Raj (Journal of College of Medical Sciences-Nepal, 2024)
Background International Prostate Symptom Score (IPSS) is a widely used as a standard, despite the fact that many patients find it time-consuming and confusing. Recent years have seen the development of a Visual Prostate Symptom Score (VPSS), which is thought to be easier and more comprehensible by patients with lower educational status. Methods This is a qualitative comparative cross sectional study conducted at College of Medical Sciences, Bharatpur Chitwan, from December 2023 to February 2024. Both the IPSS and the VPSS were used to evaluate all of the symptoms, and uroflowmetry values were also collected. Comparisons between the IPSS and VPSS and with uroflowmetry parameters were made. Results Mean age of the patients was 63.85 years and mean prostate volume was 31.67 gm. Both the results of the total VPSS vs. total IPSS (r = 0.96, p = 0.001) and the VPSS QoL vs. IPSS QoL score (r = 0.97, p = 0.001) showed a high positive connection. There were statistically significant positive correlations between the results of the following tests: VPSS weak stream vs IPSS weak stream (r = 0.87, p < 0.001), VPSS daytime frequency vs IPSS daytime frequency (r = 0.89, p < 0.001), VPSS nocturia vs IPSS nocturia (r = 0.92, p < 0.001), VPSS total vs VPSS QoL score (r = 0.88, p < 0.001), IPSS total vs IPSS QoL score (r = 0.91, p < 0.001). Conclusions When patients with BEP presents with LUTS, the VPSS is a simple and reliable tool to evaluate the severity of the symptoms. Its usefulness in assessing LUTS in patients with lower educational status is an additional benefit.